Intellectual (Neo-) Imperialism: The Examples of “Islam[ism(s)]” and “Jihad[ism(s)]” - Carimo Mohomed (SIASAT, 2022)
In any scientific endeavour, or considered as such, methodology and epistemology are paramount, not to mention ontology: what is the nature of the reality that we are studying? What is the nature of the knowledge that is being produced and its rationality? What are the methods applied to the field of study? However, when it to comes to “Islam”, the “Middle East”, or the “Orient”, the starting points are assumptions and truisms, particularly in “scientific” fields such as Political Science or International Relations, especially when the subject is the relation between politics and religion. In the last few decades, Islam has become a central point of reference for a wide range of political activities, arguments and opposition movements. The term “political Islam”, or “Islamism”, has been adopted by many scholars in order to identify this seemingly unprecedented irruption of Islamic religion into the secular domain of politics and thus to distinguish these practices from the forms of personal piety, belief, and ritual conventionally subsumed in Western scholarship under the unmarked category “Islam”. There have been tremendous, innumerable websites, voluminous publications and many projects on “Islamism(s)” and “Post-Islamism(s)”, the idea that political Islam had failed. However, when reality did not confirm that prediction, a new term was coined: “neo-Islamism”. This paper aims to explore the thesis that, as in other fields, these labels are nothing more than an attempt by Area Studies within Western academia to mould reality according to preconceived ideas and according to policy-oriented circles and funded by governmental organizations, and that, when dealing with “Islam” and “politics”, we are urgently in need of a different epistemology.